Komunikasi dengan Pendekatan HOTS dalam Pendidikan Anak Usia Dini pada Abad 21 - Elvita Rahmi; Dewi Nazwa Aliyah; Nuzul Hidayah; Marlina Marlina (CV. Alim's Publishing, 2026)
This study aims to analyze the implementation of communication using the Higher Order Thinking Skills (HOTS) approach in Early Childhood Education (ECE) learning in the 21st century. The HOTS approach is a learning strategy that emphasizes critical thinking, creativity, problem-solving, and decision-making through interactive communication between teachers and children. This study employed a qualitative approach using a library research method by reviewing relevant books, scientific journals, and educational documents related to communication and HOTS-based learning. The findings indicate that effective two-way communication creates an active, enjoyable, and child-centered learning environment that encourages children to ask questions, express opinions, participate in discussions, and solve problems according to their developmental stages. Teachers play an essential role as facilitators by providing stimulation through open-ended questions, discussions, and exploratory learning activities to foster higher-order thinking skills. Furthermore, HOTS-based communication supports children's language, social, and emotional development while enhancing their learning participation and preparing them to face the challenges of 21st-century education.